STEM-AR Based Ecology and Biodiversity E-book Development for Increasing Students' Scientific Reasoning - Ina Ana Khoeriah; Irvan Permana; Indarini Dwi Pursitasari (Postgraduate, University of Mataram, 2023)
This research aims to developing STEM-AR-based e-book teaching materials to improve students' scientific reasoning in ecology and biodiversity materials. The development of this research is important as a parameter of 21st-century abilities, which require students to have 4C abilities to face the education era of 4.0. This research method uses Research and Development (R&D). The R&D design chosen was Thiagarajan design consisting of four stages (Define, Design, Develop, and Disseminate) (Thiagarajan, 1974). Class VII students (N = 42) were involved as research subjects who were taken by the purposive sampling technique. Data collection was carried out through scientific reasoning tests, student response questionnaires, and observation sheets. Data processing techniques used paired sample T-tests and then performed the N-gain test. The results of the analysis show that after using the STEM-AR-based e-book, there is an increase in scientific reasoning ability, with an N-Gain value of 63% in the medium category. Testing the effectiveness of teaching materials using the SPSS paired sample t-test showed a result of 0.001, which means that STEM-AR-based teaching materials affect students' scientific reasoning. The descriptive average of scientific reasoning has increased by 40%. In addition, students gave positive responses to teaching materials, which made it easier to understand the material